The Role of Mead's Symbolic Interactionism in Understanding the Dynamics of Individual Health Beliefs and Collective Healthy Behavior in Jatinangor - Setiawan (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2025)
Healthy behavior is a main pillar in realizing Healthy Indonesia 2030, where the behavior needs to be internalized both individually and collectively. This effort is supported by various health facilities, from primary to tertiary services, to facilitate prevention, treatment, and early detection of disease. This study aims to examine and examine aspects of health beliefs in shaping healthy behavior in the Jatinangor community, using the lens of George Herbert Mead's Symbolic Interactionism Theory. This perspective highlights how the meaning of healthy behavior is constructed through social interaction, how individuals interpret the role of 'The Generalized Other' (society) in shaping collective healthy behavior, and how symbolic processes (such as communication and interpretation of cues) influence individual health beliefs. This qualitative study used in-depth interviews, observations, and Focus Group Discussions (FGD) to collect data. The results showed that the majority of informants had strong healthy behavior beliefs, reflected by high perceived susceptibility and strong perceived benefits of preventive measures. Another key finding was the significant role of supportive communities, healthy lifestyle promotion, and respect for others in improving psychological well-being, all of which are manifestations of symbolic interaction processes. In conclusion, individual beliefs, self-regulation, motivation, social support, and mindsets which are formed and strengthened through symbolic interaction play a crucial role in achieving physical and emotional well-being. Based on these findings, it is recommended that health programs in Jatinangor District focus more on strengthening the role of communities and peer support groups, given the significant influence of social support in constructing collective healthy meanings and behaviors.